Littering Activities Monitoring using Image Processing - Husni, Nyayu Latifah; Handayani, Ade Silvia; Passarella, Rossi; Abdurrahman; Rahman, A.; Felia, Okta (Computer Engineering and Applications Journal (ComEngApp), 2023)
Littering is a human behavior that become a habit since childhood. Even though there are rules that prohibit this behavior, the community still continues to do so. In order to limit this bad behavior, a device that can monitor and provide notifications is needed. In this research, proposed device can identify human activities by utilizing webcam-based image processing. It is processed by machine learning using the Recurrent Neural Network (RNN). The monitoring device produced in this research works by comparing the captured image data with dataset. The captured image data are extracted into figures and form several coordinate points on the human body. Then, the system classifies the human activities into two categories, i.e., normal or littering. This device will provide an output in the form of a ewarning every time the activity of littering is detected.